Transportation System Development and Challenge in Jakarta Metropolitan Area, Indonesia - Farda, Muhammad; Lubis, Harun (http://dx.doi.org/10.31427/IJSTT.2018.1.2.2, 2018)
Jakarta Metropolitan Area has been facing problem in terms of congestion and its chain effect, namely time value loss, high fuel consumption, and high greenhouse gas emission. The problem is caused by many factors, namely high population, high use of the private vehicle, inadequate current public transport supply, urban sprawling, etc. The government, both City and National Government has been formulating and implementing a plan to develop sustainable transportation that serves the citizen of Jakarta Metropolitan Area. This included the operation of Jakarta Bus Rapid Transit, KRL Commuter Line and Jakarta Mass Rapid Transit. In the near future, both inner city and metropolitan light rapid transit will also operate in this area. This paper reviews the development and challenge of the transportation system in Jakarta Metropolitan Area and proposes a recommendation to optimize the current transport system. In general, there are three components that should be considered to achieve sustainable transportation. Those components are i) strong transport authority, ii) integrated master plan, iii) Sustainable Resources, Funding, and Financing.